PENGARUH KEADILAN ORGANISASI DAN PERCEIVED ORGANIZATIONAL SUPPORT (POS) TERHADAP PERILAKU KONTRAPRODUKTIF GURU SD NEGERI DI KECAMATAN BEJI KOTA DEPOK PROVINSI JAWA BARAT - Indah Wijayanti (Jurnal Manajemen Pendidikan, 2014)
The purpose of this research is to comprehensively understand about the effects of organizational justice and perceived organizational support (POS) on counterproductive work behavior. The research has been conducted at elementary state schools in Depok, West Java. The research methodology used was a survey method with data analysis of path analysis. The respondents were 107 out of 146 total teachers which were selected at a simple random way. Analysis and interpretation of the data indicate that: (1). Organizational justice has a negative direct effect of on the counterproductive work behavior. (2). Perceived organizational support (POS) has a negative direct effect on the counterproductive work behavior, and (3). Organizational justice has a positive direct effect on the perceived organizational support (POS).